Language Didactics Dissertations in Sweden 2000 – 2009: A Research Survey - Jörgen Tholin (Moderna Språk)
This article surveys doctoral dissertations in language education written in Sweden over the ten years from 2000 to 2009. The survey concentrates on foreign languages. 23 dissertations are studied, 12 dealing with English, five with French, two with German, one with Spanish, one with Italian, and two with no specific language. Eighteen of the dissertations principally deal with years seven to nine of primary/lower-secondary school and with upper-secondary school, two deal with language studies at university level, and one deals with upper-secondary school and university. The article ends with a short follow-up on the researchers surveyed and the research they have conducted since writing their dissertations.